Can productivity still grow in service-based economies? Literature overview and preliminary evidence from OECD countries - Sorbe, Stéphane; Gal, Peter N.; Millot, Valentine (Paris, 2018)
"Services employ an ever-increasing share of workers in all OECD countries. This trend is likely to continue as it reflects deep structural forces, such as increasing consumption of services with rising incomes and population ageing and the growing role of intangible assets. Services are very diverse, but overall tend to have weaker productivity levels and growth rates than manufacturing. As a result, the shift to services entails a moderate but persistent drag on productivity growth. Still, there are reasons to hope for a pick-up in service productivity in the future, including thanks to new technologies (e.g. digital platforms, artificial intelligence). This concerns both “knowledge intensive” services (e.g. information and communication) and less knowledge intensive ones (e.g. personal transport). Harnessing this productivity potential requires adjusting policies to foster innovation and efficient use of new technologies, enhance competitive forces by reducing information asymmetries, barriers to entry and switching costs, and increase the tradability of services within countries and across borders."